Catalytic wet air oxidation of phenol with functionalized carbon materials as catalysts：Reaction mechanism and pathway - Wang, Jianbing; Fu, Wantao; He, Xuwen; Yang, Shaoxia; Zhu, Wanpeng (Journal of environmental sciences (China), 2014)
The development of highly active carbon material catalysts in catalytic wet air oxidation（CWAO）has attracted a great deal of attention. In this study different carbon material catalysts（multi-walled carbon nanotubes,carbon fibers and graphite） were developed to enhance the CWAO of phenol in aqueous solution. The functionalized carbon materials exhibited excellent catalytic activity in the CWAO of phenol. After 60 min reaction,the removal of phenol was nearly100% over the functionalized multi-walled carbon,while it was only 14% over the purified multi-walled carbon under the same reaction conditions. Carboxylic acid groups introduced on the surface of the functionalized carbon materials play an important role in the catalytic activity in CWAO. They can promote the production of free radicals,which act as strong oxidants in CWAO. Based on the analysis of the intermediates produced in the CWAO reactions,a new reaction pathway for the CWAO of phenol was proposed in this study. There are some differences between the proposed reaction pathway and that reported in the literature. First,maleic acid is transformed directly into malonic acid. Second,acetic acid is oxidized into an unknown intermediate,which is then oxidized into CO2 and H2O. Finally,formic acid and oxalic acid can mutually interconvert when conditions are favorable.